2017
DOI: 10.4240/wjgs.v9.i7.167
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors - especially different types of plexitis - for postoperative relapse in Crohn’s disease

Abstract: AIMTo evaluate the presence of submucosal and myenteric plexitis and its role in predicting postoperative recurrence.METHODSData from all patients who underwent Crohn’s disease (CD)-related resection at the University of Szeged, Hungary between 2004 and 2014 were analyzed retrospectively. Demographic data, smoking habits, previous resection, treatment before and after surgery, resection margins, neural fiber hyperplasia, submucosal and myenteric plexitis were evaluated as possible predictors of postoperative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…As several studies have identified the presence of plexitis in the proximal margin of intestinal resections as a powerful tool to predict relapse (Ryan et al, 2019), the accumulation of immune cells in and around the nerve enteric ganglia or bundle, has been recognized as a marker of post-operative recurrence in case of Crohn's disease (Gionchetti et al, 2017). Attempts to characterize the plexitis describe the presence of mast cells, eosinophils and T lymphocytes infiltrating the submucosal and/or myenteric plexus (Bressenot et al, 2013;Decousus et al, 2016;Ferrante et al, 2006;Lemmens et al, 2017;Milassin et al, 2017;Misteli et al, 2015;Sokol et al, 2009). However, little is known about the enteric neural cells involved in plexitis.…”
Section: Introductionmentioning
confidence: 99%
“…As several studies have identified the presence of plexitis in the proximal margin of intestinal resections as a powerful tool to predict relapse (Ryan et al, 2019), the accumulation of immune cells in and around the nerve enteric ganglia or bundle, has been recognized as a marker of post-operative recurrence in case of Crohn's disease (Gionchetti et al, 2017). Attempts to characterize the plexitis describe the presence of mast cells, eosinophils and T lymphocytes infiltrating the submucosal and/or myenteric plexus (Bressenot et al, 2013;Decousus et al, 2016;Ferrante et al, 2006;Lemmens et al, 2017;Milassin et al, 2017;Misteli et al, 2015;Sokol et al, 2009). However, little is known about the enteric neural cells involved in plexitis.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Similarly, myenteric plexitis at the proximal resection margin is associated with an increased risk of endoscopic and surgical relapse. 35,36,[39][40][41] Finally, some studies suggest that reduced density of lymphatic vessels is associated with postoperative recurrence. 36,42 Regardless of the extent of surgery, 25 to 75% of patients will develop endoscopic recurrence within one year of surgery, often just proximal to the surgical anastomosis.…”
mentioning
confidence: 99%
“…17 Studies have shown that at least 1 eosinophil and 6 lymphocytes in SMP predicted surgical recurrence whereas at least 1 lymphocyte in SMP or MP predict endoscopic, clinical and surgical recurrence. [19][20][21][22] The hazard ratio of surgical, endoscopic, and clinical recurrence were 9, 6, and 4, respectively, in the presence of plexitis on time to event analysis. 1 Overall 4 studies also reported a 30% higher risk of early endoscopic recurrence (<12 months) with plexitis.…”
Section: ) Plexitis (P)mentioning
confidence: 96%
“…11,[13][14][15][16][17][18] On multivariate analysis, plexitis was associated with 10-fold higher risk of endoscopic recurrence and a 30% higher risk of surgical recurrence. 12,19 Plexitis in MP and not SMP was associated with an increased risk of endoscopic recurrence when assessed by hematoxylin and eosin staining alone. 17 Studies have shown that at least 1 eosinophil and 6 lymphocytes in SMP predicted surgical recurrence whereas at least 1 lymphocyte in SMP or MP predict endoscopic, clinical and surgical recurrence.…”
Section: ) Plexitis (P)mentioning
confidence: 97%
See 1 more Smart Citation